Molecular and microscopy detection of Pneumocystis jirovecii in hospitalized patients during the COVID-19 pandemic - Matouri, Roya; Aboutalebian, Shima; Nasri, Elahe; Sadeghi, Somayeh; Rostami, Soodabeh; Fakhim, Hamed; Ghafel, Safiyeh; Hosseini, Mahnaz; Mousavi, Somayeh; Rouhi, Faezeh; Pestechian, Nader; Mirhendi, Hossein (Frontiers in Medicine, 2023)
Introduction Early detection of Pneumocystis jirovecii as an opportunistic pathogen that may endanger predisposed persons, including COVID-19 patients, may help to choose the optimal management. Methods In this study, 585, including 530 COVID-19 patients, with clinical and radiological evidence of respiratory diseases, were investigated for P. jirovecii screening. Clinical specimens were examined by direct microscopy and PCR, and randomly selected positive PCR products were confirmed through DNA sequence analysis. Results Thirty-one (5.3%) samples were positive in P. jirovecii-specific nested-PCR, while by direct microscopic tests, Pneumocystis was observed in 22 (3.76%) samples. Males (61.7%) and patients over 50 years old (75.6%) were more commonly affected than others, and malaise and fatigue (84%), and wheezing (75%) were the most common symptoms, followed by fever (40.48%) and dyspnea (39.51%). Among the Pneumocystis-positive patients, three cases had coinfection with Aspergillus fumigatus, A. flavus, and A. niger (each n = 1), as documented by direct microscopy, culture, and species identification by PCR-sequencing. Conclusion Pneumocystis pneumonia is still a diagnostic challenge; therefore, additional large-scale studies are needed to clarify the epidemiology of the disease in immunocompromised or COVID-19 patients.